Hand Gesture Interaction with Human-Computer (Global Journal of Computer Science and Technology, 2011)
Hand gestures are an important modality for human computer interaction. Compared to many existing interfaces, hand gestures have the advantages of being easy to use, natural, and intuitive. Successful applications of hand gesture recognition include computer games control, human-robot interaction, and sign language recognition, to name a few. Vision-based recognition systems can give computers the capability of understanding and responding to hand gestures. The paper gives an overview of the field of hand gesture interaction with Human- Computer, and describes the early stages of a project about gestural command sets, an issue that has often been neglected. Currently we have built a first prototype for exploring the use of pieand marking menus in gesture-based interaction. The purpose is to study if such menus, with practice, could support the development of autonomous gestural command sets. The scenario is remote control of home appliances, such as TV sets and DVD players, which in the future could be extended to the more general scenario of ubiquitous computing in everyday situations. Some early observations are reported, mainly concerning problems with user fatigue and precision of gestures. Future work is discussed, such as introducing flow menus for reducing fatigue, and control menus for continuous control functions. The computer vision algorithms will also have to be developed further.
Keywords: Human Computer Interaction; Hand Tracking; Hand gesture; Computer Vision Based Gesture Recognition; HCI; Gesture Command; Marking Menu